Perspectives and Problems in Sustainable Development - Sánchez, Antoni (Problemy Ekorozwoju, 2008)
Sustainable development has undergone an important evolution over recent years. It has been used not only as a tool to decide among several options in research programs but also in political decisions. However, how can we measure if something is sustainable or not? It seems that Life Cycle Assessment (LCA) is the most powerful technique to objectively describe and determine the sustainability of a new project, idea, change in established lines, etc. However, some important aspects are lacking today in LCA, for instance, experimental data on environmental impact related to emission factors. In sustainable development, global warming is presented today as the major reason to carry out sustainability studies. Although global warming is, of course, an important reason for attaining sustainability, it is not the only reason. In this work, relevant aspects related to two important topics involved in modern sustainable development, sustainable tourism and waste management are briefly introduced.